Atom transfer radical polymerization in dispersed media with low-ppm catalyst loading. (9th May 2023) - Wang, Yi; Lorandi, Francesca; Fantin, Marco; Matyjaszewski, Krzysztof
Abstract: Polymerizations in aqueous dispersed media benefit from good heat transfer, low viscosity, low content of volatile compounds, and established industrial use. Over the past two decades, the implementation of ATRP in dispersed media highlighted the possibility of achieving improved livingness and producing a variety of macromolecular architectures. With the introduction of several methods for activator regeneration in ATRP, catalyst loading has been greatly diminished, and the reaction setup has been simplified. The availability of ATRP techniques employing low-ppm (part per million) catalyst loadings enabled to access an even larger variety of polymer architectures and functional polymer particles, which have been applied for molecular recognition, drug delivery, bio-quantification, and advanced coatings. This minireview presents innovative synthetic approaches, polymer architectures, and relevant applications, as well as the challenges that remain to be overcome to promote the industrialization of ATRP in dispersed media. Graphical abstract: Image 1 Highlights: ATRP in dispersed media achieved improved livingness and produced a variety of macromolecular architectures. Catalyst loading was greatly diminished to a low ppm level. ATRP in dispersed media benefits from good heat transfer, low viscosity, low VOC content, and established industrial use.